The Influence of Antioxidants on Oxidative Stress-Induced Vascular Aging in Obesity - Hiva Sharebiani; Shayan Keramat; Abdolali Chavoshan; Bahar Fazeli; Agata Stanek (MDPI AG, 2023)
Obesity is a worldwide trend that is growing in incidence very fast. Adipose tissue dysfunction caused by obesity is associated with the generation of oxidative stress. Obesity-induced oxidative stress and inflammation play a key role in the pathogenesis of vascular diseases. Vascular aging is one of the main pathogenesis mechanisms. The aim of this study is to review the effect of antioxidants on vascular aging caused by oxidative stress in obesity. In order to achieve this aim, this paper is designed to review obesity-caused adipose tissue remodeling, vascular aging generated by high levels of oxidative stress, and the effects of antioxidants on obesity, redox balance, and vascular aging. It seems that vascular diseases in obese individuals are complex networks of pathological mechanisms. In order to develop a proper therapeutic tool, first, there is a need for a better understanding of interactions between obesity, oxidative stress, and aging. Based on these interactions, this review suggests different lines of strategies that include change in lifestyle to prevent and control obesity, strategies for adipose tissue remodelling, oxidant-antioxidant balance, inflammation suppression, and strategies against vascular aging. Some antioxidants support different lines of these strategies, making them appropriate for complex conditions such as oxidative stress-induced vascular diseases in obese individuals.